Highly-ordered nanoporous anodic aluminum oxide films - Voloshko, A.V.; Danilina, V.V.; Mateychenko, P.V.; Bespalova, I.I. (Functional Materials, 2012)
The samples of the nanostructured aluminum oxide films were obtained by anodic oxidation method (thickness is near 100 μm and dpores = 42+4 nm). Two stage aluminum oxidation was carried out in a two electrode electrochemical cell at 0°C and the voltage value of 40 V. Oxalic acid solution was used as an electrolyte. The optimal heat treatment conditions, of the weak luminescent films without destruction of the order structure have been proposed. Зразки плівок наноструктурованого окису алюмінію товщиною 100 мкм та розміром пор dпор = 42±4 нм отримано за допомогою методу анодного окиснсння. Двостадійне окиснсння алюмінію проводилося у двоелектродній комірці при 0°С при напрузі 40 В, у якості електроліту використано розчин щавлевої кислоти. Обрано оптимальні умови термообробки для одержання нелюмінeсцeнтних плівок без порушення високовпорядкованої структури. Образцы пленок наноструктурированного оксида алюминия толщиной 100 мкм и размером пор dпор = 42±4 нм получены при помощи метода анодного окисления. Двух стадийное окисление алюминия проводилось в двухэлектродной электрохимической ячейке при 0°С и напряжении 40 В, в качестве электролита использован раствор щавелевой кислоты. Выбраны оптимальные условия термообработки для получения оптически прозрачных образцов без нарушения высокоупорядоченной структуры.